2019
DOI: 10.3171/2018.2.jns172361
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife stereotactic radiosurgery for cavernous sinus meningioma: long-term follow-up in 200 patients

Abstract: OBJECTIVE The authors of this study evaluate the long-term outcomes of stereotactic radiosurgery (SRS) for cavernous sinus meningioma (CSM). METHODS The authors retrospectively assessed treatment outcomes 5-18 years after SRS in 200 patients with CSM. The median patient age was 57 years (range 22-83 years). In total, 120 (60%) patients underwent Gamma Knife SRS as primary management, 46 (23%) for residual tumors, and 34 (17%) for recurrent tumors after one or more surgical procedures. The median tumor target v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 31 publications
4
38
1
Order By: Relevance
“…The reported tumour control after proton beam RT is ranged from 90 to 96% at 5 years, similar to that observed with fractionated photon techniques (Table 2) [43,44]. The reported actuarial control rates after SRS is in the range of 90-95% at 5 years and 80-90% at 10 and 15 years using a median margin dose to the tumour of 13-15 Gy, with a variable improvement of neurological functions in up to 60% of patients [45][46][47][48][49][50][51][52][53][54][55][56]. The rate of significant complications at doses of 13-15 Gy is < 10%, being represented by either transient or permanent complications [45,51].…”
Section: Results Of Radiation Treatments In Parasellar Tumourssupporting
confidence: 68%
“…The reported tumour control after proton beam RT is ranged from 90 to 96% at 5 years, similar to that observed with fractionated photon techniques (Table 2) [43,44]. The reported actuarial control rates after SRS is in the range of 90-95% at 5 years and 80-90% at 10 and 15 years using a median margin dose to the tumour of 13-15 Gy, with a variable improvement of neurological functions in up to 60% of patients [45][46][47][48][49][50][51][52][53][54][55][56]. The rate of significant complications at doses of 13-15 Gy is < 10%, being represented by either transient or permanent complications [45,51].…”
Section: Results Of Radiation Treatments In Parasellar Tumourssupporting
confidence: 68%
“…9,15,25 Some recent studies that were focused on the treatment of intracranial meningiomas with radiosurgery reported that the local tumor control rates ranged from 88% to 100%, in which 19%-74% of tumors shrank during a mean follow-up of 36-78 months. 3,7,12,21,22,[30][31][32][33][34]37,[39][40][41] In a single-center study, Hasegawa et al 12 reported an actuarial PFS rate of 92%, 86%, and 72% at 3, 5, and 10 years, respectively, in 67 patients. In a meta-analysis of SRS for skull base meningiomas, Starke et al 41 reviewed the outcome in 469 patients with large skull base meningiomas (> 8 cm) from several centers, and reported that the actuarial tumor PFS rates at 3, 5, and 10 years were 90.3%, 88.6%, and 77.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Parameters of tumor control were defined as 1) tumor progression (tumor volume increased ≥ 10% compared to the volume at GKRS); 2) tumor regression (tumor volume shrinkage ≥ 10%); or 3) tumor unchanged (tumor volume change < 10%). 5,30,34 There was no distant metastasis. Tumor volume was computed by measuring the maximum diameter at the horizontal, coronal, and sagittal planes of the MR images.…”
Section: Clinical and Radiological Follow-upmentioning
confidence: 93%
See 1 more Smart Citation
“…In WHO grade I parasellar meningiomas, the outcome of radiosurgery is favorable [105][106][107][108][109]. The long-term recurrence rate also appears to be favorable but remains uncertain [110]. The risk of remote recurrence is persistent, whereas the risk of tumor transformation remains uncertain.…”
Section: Stereotactic Radiosurgerymentioning
confidence: 99%